HUBUNGAN OVERWEIGHT DENGAN KEJADIAN CHF (CONGESTIVE HEART FAILURE) DI RUANG RAWAT INAP RUMAH SAKIT RIZANI PAITON PROBOLINGGO - Irani, Yunita; Sholehah, Baitus; Khotimah, Husnul (NHM PRESS, 2024)
Background: Congestive Heart Failure (CHF) is a growing health problem with high mortality and morbidity rates in both developed and developing countries. At Rizani Paiton Hospital Probolinggo, CHF is among the top ten most common cases. Overweight is one of the factors that worsen the condition of CHF patients, measured through Body Mass Index (BMI). Objective: To determine the relationship between overweight and the incidence of CHF in the inpatient ward of Rizani Paiton Hospital Probolinggo. Methods: This analytical study used direct observation and Gamma correlation analysis, involving 60 patient samples. Results: The significance value (sig) of 0.000 (p < 0.05) indicates a very significant correlation between overweight and the incidence of CHF. The correlation value of 0.922 shows a very strong and positive relationship, meaning that the higher the patient's BMI, the greater the risk of CHF. Conclusion: Overweight has a significant correlation with the incidence of CHF. Weight management is important as a preventive measure against CHF. Dietary control is necessary to reduce the risk of CHF.